Color-difference assessment and enhancement for driving headlight simulation. (May 2016) - Vidal, Quentin; Michelin, Sylvain; Laborie, Baptiste; Kemeny, Andras
Real-time headlight simulation in driving conditions is used by most car manufacturers to assure the quality, cost, and delivery of headlight engineering design. An important parameter judged by the headlight assessment team is color restitution; indeed, this parameter has to meet the standard of "lamps for road vehicles." Therefore, the goal of this study was the color assessment and enhancement of a driving headlight simulator. For this purpose, this study was conducted in two phases: the process of constructing two color acceptability scales that directly reflect the perception of two different populations (experts and "naive"), and the assessment of a method based on the chromatic adaptation transform (CAT) for reducing the color difference between real and virtual environments. In the first phase, we conducted two psychophysical experiments (i.e., one for each population), in which the observers had to report their degree of satisfaction about the color difference. These two experiments enabled the creation of two acceptability scales for headlight simulation. In the second phase, we compared the performance of different chromatic transformations; as a result of this comparison, we advise the use of the CAT02 transformation, in order to reduce the color difference for headlight assessment in driving simulation experiments.